PERTANGGUNGJAWABAN HUKUM DOKTER PADA KASUS MALPRAKTIK: KAJIAN TEORITIS DAN PRAKTIS - REYZA MUHAMMAD REYZA PRATAMA (Jurnal Kedaulatan Hukum, 2026)
Medical malpractice remains one of the most persistent legal and ethical challenges within Indonesia’s health-care system, particularly as public awareness of patients’ rights continues to grow. This paper examines the legal liability of medical doctors in malpractice cases and analyzes how the existing legal framework functions to ensure fairness for both patients and medical practitioners. The study aims to provide a comprehensive overview of the mechanisms of legal accountability ethical, disciplinary, civil, and criminal while highlighting the issues that often arise in determining whether a medical error constitutes malpractice or an unavoidable medical complication. Using a normative legal research method supported by statutory, conceptual, and comparative approaches, this article analyzes various laws, regulations, and recent scholarly works in the field of health law. The findings demonstrate that Indonesia’s multi-layered system of accountability is designed to balance patient protection with the professional autonomy of physicians; however, inconsistencies in implementation, limited legal literacy among medical personnel, and weaknesses in documentation practices continue to hinder effective enforcement. This study contributes to the development of legal discourse by offering a structured analysis of doctor liability and reaffirming the importance of clear standards, improved legal awareness, and stronger regulatory integration. These insights are expected to support future academic discussions and policymaking efforts related to medical malpractice in Indonesia.